Control of Turbulence in a Multiple-Fan Wind Tunnel: Part 2, Simulation of Atmospheric Turbulence Power Spectra - KIKUGANA, Hironori; NISHI, Akira; MIYAGI, Hironori; Shuyang, CAO; MATSUDA, Yuji (Wind Engineers, JAWE, 1999)
In order to investigate the wind effects on large structures, such as high-rise buildings, long suspension bridges, etc., new-type multiple-fan wind tunnels are being developed in our laboratory In these tunnels, flow turbulence has been actively generated by multiple-fans and oscillating airfoils. Usually, a wide range of power spectrum can be observed in an atmospheric turbulence under neutral conditions. Therefore, the corresponding large-scale turbulence should be reproduced to simulate the atmospheric turbulence in the tunnel. As a result of the experiments, a wide range of power spectra was achieved in the tunnel, and it was shown clearly that these spectra were well fitted to Kolmogorov's law. This means that a wide range of the inertial subrange corresponding to the atmospheric turbulence was observed.